PENGAMBILAN KEPUTUSAN DALAM PEMILIHAN SAYURAN DAN POLA KONSUMSI SAYURAN RUMAH TANGGA PETANI SAYURAN DI DESA GISTING ATAS KECAMATAN GISTING KABUPATEN TANGGAMUS - Dian Widya Putri; Wuryaningsih Dwi Sayekti; Kordiyana K Rangga (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This research aimed to analyze the decision-making process on the vegetables food choise, the pattern of processed vegetables consumption, and factors that affected the amount of vegetables consumption among households (HH) at Gisting Atas Village. This research was conducted by survey method. Location of this research was determined purposively at Gisting Atas Village Gisting Subdistrict of Tanggamus district. The amount of research samples was as many as 65 HH who were selected by simple random sampling. The data was collected in month of April 2018. The result showed that HH decision making on processed local food consisted of introduction needs, seeking information, evaluation of the alternative, selection and consumption decision, post-selection evaluation. Cabbage and kale vegetables were the most consumed vegetables in which frequency was in sufficient category. The level of education and nutrition knowledge of housewives significantly influenced the amount of vegetables consumption.Key words: consumtion pattern, decision making, vegetables consumption